(untitled) (Applied Biological Research, 2018)
A study was carried out to assess the effects of drying methods and chemical pretreatments on product quality of chilli, Capsicum annum, (var. Kashmir Long-1). Pretreated chilli was open sun-dried and solar tunnel dried upto optimum moisture levels and assessed for various physicochemical changes. The results revealed that among the pretreated samples, 2.5% potassium carbonate + 1% ground nut oil + 0.1% gum acacia + 0.001% butylated hydroxy anisol L-1for 15 min had highest ascorbic acid (41.08 mg 100 g-1), capsaicin (1.077% db) and reducing sugar (0.617% db) contents; and lowest moisture (9.85%) and non-enzymatic browning (0.123) values. All the treatments significantly enhanced the L* (31.56), a* (25.23), b* (13.44), C* (27.35), h* (27.6) and ΔE* (3.89) values in solar tunnel-dried samples. However, in sun-dried samples lower ascorbic acid (39.98 mg 100 g-1), capsaicin (0.939% db) and reducing sugar (0.591% db) contents and higher moisture (10.43%), non-enzymatic browning (0.146), L* (30.52), a* (24.23), b* (12.68), C* (28.59), h* (28.0), and ΔE* (3.86) values were observed. Drying time of solar tunnel-dried samples was 48 h as compared to 72 h in case of sun-dried samples. The most efficient drying method was solar tunnel drying as it retained the nutritional properties and colour characteristics and reduced the drying time.